Education and Monitoring: what did the “Performance-Budget Law” in Ceará teach us? (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
The following study aims to analyze the 14.023/2007 State of Ceará Act, which has established new criteria to calculate each piece of ICMS – a type of Ceará tax – among the municipalities (a type of “Performance-Budget Law”). By changing the former division model and after a public management by results paradigm, this new legislation has introduced an induced competition between the education managers, since an improvement at education numbers would provide higher incomes. Therefore, the study attempts a qualitative and comparative analyses between the best and worse cities in 2009, when the policy started its enforcement, basing on IDEB numbers – a federal evaluation over public education. So, we processed the official data to calculate each ICMS share received by the municipality, monthly, between January 2009 until December 2020, as well, annually, each education index to calculate this share. By comparing those data, we can measure the policy’s impact on each municipality and rethink the logic model of public policy evaluation, after the State of Ceará experience.